Restrictive Versus Massive Fluid Resuscitation Strategy (REFILL study), influence on blood loss and hemostatic parameters in obstetric hemorrhage: study protocol for a randomized controlled trial - Natascha de Lange (Trials, 2018)
Abstract Background Postpartum hemorrhage (PPH) is associated with maternal morbidity and mortality and has an increasing incidence in high-resource countries, despite dissemination of guidelines, introduction of skills training, and correction for risk factors. Current guidelines advise the administration, as fluid resuscitation, of almost twice the amount of blood lost. This advice is not evidence-based and could potentially harm patients. Methods All women attending the outpatient clinic who are eligible will be informed of the study; oral and written informed consent will be obtained. Where there is more than 500 ml blood loss and ongoing bleeding, patients will be randomized to care as usual, fluid resuscitation with 1.5–2 times the amount of blood loss or fluid resuscitation with 0.75–1.0 times the blood loss. Blood loss will be assessed by weighing all draping. A blood sample, for determining hemoglobin concentration, hematocrit, thrombocyte concentration, and conventional coagulation parameters will be taken at the start of the study, after 60 min, and 12–18 h after delivery. In a subgroup of women, additional thromboelastometric parameters will be obtained. Discussion Our hypothesis is that massive fluid administration might lead to a progression of bleeding due to secondary coagulation disorders. In non-pregnant individuals with massive blood loss, restrictive fluid management has been shown to prevent a progression to dilution coagulopathy. These data, however, cannot be extrapolated to women in labor. Our objective is to compare both resuscitation protocols in women with early, mild PPH (blood loss 500–750 ml) and ongoing bleeding, taking as primary outcome measure the progression to severe PPH (blood loss > 1000 ml). Trial registration Netherlands Trial Register, NTR 3789. Registered on 11 January 2013.